Meaningful Work and Counterproductive Work Behavior of Automotive Company’s Employees in Cikarang - Marlina Bhekti Hatmanto; Yusak Novanto (Merpsy Journal, 2026)
The automotive industry requires competent and responsible employees, yet counterproductive work behavior (CWB) remains a concern among production workers. Although meaningful work has been proposed as a factor that may reduce CWB, findings from previous studies remain inconsistent, particularly in manufacturing settings. This study examined the relationship between meaningful work and CWB among 228 production employees in an automotive company in Cikarang, Indonesia. A quantitative correlational design with total population sampling was employed. Data were collected using the Work and Meaning Inventory (WAMI) and the Counterproductive Work Behavior Checklist (CWB-C). The results of Spearman’s rank-order correlation indicated no significant relationship between meaningful work and CWB (ρ = .03, p = .652). These findings suggest that meaningful work may not be directly associated with counterproductive work behavior among production employees. Future research should examine additional individual, job-related, and organizational factors that may contribute to counterproductive work behavior in manufacturing settings.